Comparison of Butter and Oleogel As Fat Replacement from Red Palm Oil With Cocoa Butter Gelator and Their Influence on The Physical and Chemical Characteristics of Gelato - Ni Made Wesi Sinta Wrdhi Warmini; Chusnul Hidayat; Rini Yanti (Indonesian Association of Food Technologists, 2023)
Red palm oil (RPO) has a high β-carotene content and can be used as a fat replacement in dairy products. However, the direct application of RPO in gelato will affect the product's physical properties. Besides that, the distinctive characteristics of RPO can also affect the sensory properties of food, reducing the product's palatability. Therefore, in this study, an oleogelation process was carried out on RPO into oleogel, which was applied to gelato. This study aimed to determine the comparison between butter and RPO oleogel with cocoa butter gelator at specific concentrations (5%, 10%, 15%) and its effect on the physical and chemical characteristics of gelato, and the percentage of the best treatment compared to control gelato. The results showed that gelato treatment affected the physical and chemical characteristics (proximate). The best gelato formulation was CBO 1 (2.1% oleogel + 2.9% unsalted butter). Then, the best oleogel percentage was CB5% (5% cocoa butter and 95% RPO gelator concentration) with an oil loss value of 18.18%±0.16. The gelato overrun value was 17.62±0.53 %; melting time was 21 minutes 42 seconds; hardness was 397.09±4.81 N, and chewiness was 58.96±0.48 N; it had a bright yellow color; viscosity before and after aging was 3435.22±14.09 cP and 4228.89±7.88 N; fat content was 4.90±0.12%; and β-carotene content was 20.67±0.19 ppm, which can be claimed as high β-carotene gelato.